Diagnosis and Management of Cholangiocarcinoma (CCA) - Hakim, Baiq Sheila Okthalia; Rahmawati, Fadila; Yuar, Alana Akmal; Setiasari, Febi Jian; Evana, Nafisya Ayu; Yolanda B.S, Moh Rizky (Jurnal Biologi Tropis, 2025)
Cholangiocarcinoma (CCA) is a malignant tumor of the biliary epithelium and represents the second most common primary liver cancer after hepatocellular carcinoma. Its incidence and mortality rates are particularly high in Asia. This review aims to provide an updated overview of risk factors, pathogenesis, diagnostic strategies, and current management of cholangiocarcinoma based on recent scientific evidence from the past decade. A narrative literature review was conducted using publications retrieved from PubMed, Scopus, and Google Scholar, limited to the last 10 years. Eligible studies included original research, systematic reviews, clinical trials, and international clinical practice guidelines addressing epidemiology, biomarkers, imaging modalities, molecular testing, as well as surgical and non-surgical treatment options. CCA is classified into intrahepatic (iCCA) and extrahepatic (eCCA: perihilar and distal). Risk factors include parasitic infections, congenital biliary anomalies, cirrhosis, viral hepatitis, and toxin exposure. Management depends on resectability: surgical resection with adjuvant capecitabine provides curative benefit, while advanced disease requires systemic chemotherapy (gemcitabine–cisplatin), second-line FOLFOX, and palliative interventions such as biliary stenting and drainage. Early detection in high-risk populations is essential to improve diagnostic accuracy and treatment outcomes. A multimodal strategy combining biomarkers, imaging, and molecular analysis enhances early recognition and guides therapy. Routine screening programs, development of novel biomarkers, and further studies on targeted therapies and immunotherapy are recommended to broaden future treatment options.